Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 2 - Section 2.7 - Derivatives and Rates of Change - 2.7 Exercises - Page 149: 38


$f(x)=e^x$ and $a=-2$

Work Step by Step

*According to definition, the derivative of a function $f$ at a number $a$ is $$f'(a)=\lim\limits_{h\to0}\frac{f(a+h)-f(a)}{h}$$ Here we have $$f'(a)=\lim\limits_{h\to0}\frac{e^{-2+h}-e^{-2}}{h}$$ Now we match the formula found above with the formula of the derivative according to definition. We find that $f(a+h)=e^{-2+h}$ and $f(a)=e^{-2}$ So, $a=-2$ and $f(a)=f(-2)=e^{-2}$ Therefore, $f(x)=e^{x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.